Biocontrol efficacy and possible mechanism of a broad-spectrum antagonistic yeast, Pichia kluyveri NY23, screened from peach fruit via microbiome analysis - Mengyang Xing; Qiu Long; Keyan Zhao; Yong Chen; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2027)

Fires reshape species-specific drought resilience of typical conifers in southwestern China - Peiyao Tao; Fen Zhang; Tian Chen; Xinglin Huang; Feifei Zhou; Keyan Fang; Xiaohua Gou; Yifei Zhao (Forest Ecology and Management, 2026)

Agglomeration under strain: Nonlinear dynamics of urban functional conflicts - Hongbo Zhao; Zeting Jia; Wenhui Yue; Yansui Liu; Qiyang Liu; Li Yue; Shaozhen Cao; Yilin Ma; Keyan Lu (Sustainable Cities and Society, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Identification of new virulence factors in Penicillium expansum via comparative transcriptomic analysis of three Penicillium species - Ting Liu; Keyan Zhao; Mengyang Xing; Yong Chen; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

An integrated framework combining deep learning and multicriteria decision-making for SDG-oriented urban low-carbon transition capacity assessment - Wentao Wang; Dezhi Li; Keyan Liu; Yongheng Zhao; Huan Zhou; Shenghua Zhou (Environmental Impact Assessment Review, 2026)

High-efficiency green management to Spodoptera frugiperda by synergistic control of pH-responsive chitosan nanoparticle-mediated RNAi and pesticide - Heng Qiao; Suman Zong; Jing Zhao; Liubin Xiao; Keyan Zhu-Salzman; Dejin Xu; Guangchun Xu; Yongan Tan (Chemical Engineering Journal, 2026)

In Vitro Characterization and Identification of Potential Probiotic Yeasts Isolated from Zaopocu, a Traditional Fermented Dregs Vinegar from Hainan Island - Lin Huang; Yuan Wang; Keyan Zhong; Ziyuan Jiang; Hengkai Jia; Shuying Chen; Zhiyuan Zhao; Xinjun Chen (Probiotics and Antimicrobial Proteins, 2025)

Achieving carrier migration pathway transformation to enhance photocatalytic moxifloxacin degradation activity by regulating the Fermi Level of g-C3N4/ ZnIn2S4 through sulfur vacancies - Han Sun; Yonghao Dong; Lei Wang; Xudong Wang; Junwei Xin; Jie Ren; Ruosong Jing; Jiayuan Yan; Yichun Xue; Keyan Zhao (Journal of Environmental Chemical Engineering, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

The negative effects of competition on tree resilience weakened as drought severity intensified - Xinyu Han; Lushuang Gao; Xianliang Zhang; Keyan Fang; Sijie Li; Keda Cui; Mengzhao Guo; Xiuhai Zhao (Agricultural and Forest Meteorology, 2025)

An Elevated Influence of the Low‐Latitude Drivers on the East Asian Winter Monsoon After Around 1990 - Bozhou Chen; Keyan Fang; Zepeng Mei; Tinghai Ou; Feifei Zhou; Hao Wu; Zheng Zhao; Deliang Chen (International Journal of Climatology, 2024)
Current East Asian winter monsoon (EAWM) indices effectively depict the associated high‐ and low‐latitude atmospheric circulations. However, the spatial dynamics of the winter coldness within the monsoon domain are not well adequately represented by EAWM indices. We introduce a novel approach to classify winter temperatures based on both their co‐variability and their mean values. We classified the EAWM domain into three distinct modes: northern (ranging from −27°C to −15°C), central (−14°C to 5°C), and southern (6°C to 27°C). The northern mode, characterised by intense coldness, correlates with a strengthened westerlies that traps Arctic cold air masses during the positive phase of the Arctic Oscillation (AO). In contrast, the southern mode is primarily influenced by low‐latitude oceanic and atmospheric patterns, particularly for near‐coast areas. The central mode, representing an interplay of both high and low‐latitude processes, encapsulates the comprehensive characteristics of the EAWM. Our analysis reveals a notable shift in the relationships among the northern, central, and southern modes around 1990. Prior to this year, the EAWM was predominantly influenced by northern atmospheric patterns, while there is a discernible increase in the influence of low‐latitude drivers afterwards. This shift may be linked to the significant warming in the western Pacific and Indian Oceans, underscoring the heightened role of low‐latitude drivers on the EAWM.

YTHDF2 phase separation promotes arsenic-induced keratinocyte transformation in a poly-m6A-dependent manner by inhibiting translational initiation of the key tumor suppressor PTEN - Tianhe Zhao; Wenxiao Xiong; Jingsilin Cai; Qian Zhang; Donglei Sun; Keyan Long; Jin Man; Zunzhen Zhang (Journal of Hazardous Materials, 2024)

A comprehensive physiological and -Omic analysis of trypsin-mediated protection of green pepper fruits from chilling injury - Keyan Zhao; Xuanqi Wang; Xiaozhen Yue; Jieyu Lv; Xiaodi Xu; Hongshan Lu; Jinhua Zuo; Xiangbin Xu; Bin Chen; Shuzhi Yuan; Qing Wang (Food Chemistry, 2024)

Enhanced antibacterial photodynamic therapy with Qu/Ce6@ZIF-8 nanoplatform for Staphylococcus aureus control in food preservation - Jianqiu Hou; Hongsu Wang; Keyan Pan; Lifang Wu; Bao Zhao (Food Bioscience, 2024)

Deciphering the transfer of hydroclimate signals to tree-ring δ18O using a proxy system model in East Asia's Meiyu region - Yesi Zhao; Huayu Lu; Keyan Fang; Peng Zhang; Deliang Chen; Achim Bräuning; Jussi Grießinger; Bao Yang; Chenghong Liang; Hongyan Zhang; Yiqian Sun; Qing Jin; et al. (Chemical Geology, 2024)

Transcriptomic, metabolomic, and physiological analysis of two varieties of Chinese cabbage (Brassica rapa L. ssp. pekinensis) that differ in their storability - Keyan Zhao; Xiaoqian Zhu; Shuzhi Yuan; Xiangbin Xu; Junyan Shi; Jinhua Zuo; Xiaozhen Yue; Tongbing Su; Qing Wang (Postharvest Biology and Technology, 2024)

N6-methyladenosine promotes aberrant redox homeostasis required for arsenic carcinogenesis by controlling the adaptation of key antioxidant enzymes - Tianhe Zhao; Donglei Sun; Keyan Long; Wenxiao Xiong; Jin Man; Qian Zhang; Zunzhen Zhang (Journal of Hazardous Materials, 2024)

RNAi-mediated plant sterol modification to control insect herbivore pests: insights from Arabidopsis and the diamondback moth - Ivy W. Chen; Robert J. Grebenok; Cheng Zhao; Li He; Jiaxin Lei; Rui Ji; Nicolo Hernandez; Joshua S. Yuan; Hisashi Koiwa; Spencer T. Behmer; Keyan Zhu-Salzman (Journal of Pest Science, 2024)

Oxidative Stress Induced by Arsenite is Involved in YTHDF2 Phase Separation - Jin Man; Qian Zhang; Tianhe Zhao; Donglei Sun; Weilian Sun; Keyan Long; Zunzhen Zhang (Biological Trace Element Research, 2024)

Spatial–temporal distribution and source analysis of atmospheric particulate-bound cadmium from 1998 to 2021 in China - Wei Huang; Donglei Sun; Tianhe Zhao; Keyan Long; Zunzhen Zhang (Environmental Geochemistry and Health, 2024)

Evaluation of the storage longevity, postharvest quality, and sugar metabolism-related gene expression in two lines (N1 and N3) of Chinese cabbage during long-term storage - Keyan Zhao; Xiaozhen Yue; Xiaoqian Zhu; Junyan Shi; Shuzhi Yuan; Hongshan lu; Xiangbin Xu; Mina Wang; Taishan Huang; Jinhua Zuo; Shuancang Yu; Qing Wang (Postharvest Biology and Technology, 2023)

Overexpression of Sly-miR167a delayed postharvest chilling injury of tomato fruit under low temperature storage - Lei Li; Xuanqi Wang; Jieyu Lv; Wenhui Duan; Taishan Huang; Keyan Zhao; Lanhuan Meng; Hongmiao Song; Qing Wang; Xiangbin Xu; Jiangkuo Li (Postharvest Biology and Technology, 2023)

An oral dsRNA delivery system based on chitosan induces G protein-coupled receptor kinase 2 gene silencing for Apolygus lucorum control - Heng Qiao; Jing Zhao; Xiaofeng Wang; Liubin Xiao; Keyan Zhu-Salzman; Jiaxin Lei; Dejin Xu; Guangchun Xu; Yongan Tan; Dejun Hao (Pesticide Biochemistry and Physiology, 2023)

N6-methyladenosine upregulates ribosome biogenesis in environmental carcinogenesis - Tianhe Zhao; Donglei Sun; Keyan Long; Bernardo Lemos; Qian Zhang; Jin Man; Manyu Zhao; Zunzhen Zhang (Science of The Total Environment, 2023)

Reconstructed Jing River streamflow from western China: A 399-year perspective for hydrological changes in the Loess Plateau - Xiaoen Zhao; Keyan Fang; Feng Chen; Hadad Martín; Fidel A. Roig (Journal of Hydrology, 2023)

Responses of the radial growth of the endangered species Keteleeria fortunei to climate change in southeastern China - Zheng Zhao; Keyan Fang; Chunfu Cao; Dai Chen; Xiaoyue Liang; Zhipeng Dong; Peng Zhang (Trees, 2019)

Interdecadal modulation of the Atlantic Multi-decadal Oscillation (AMO) on southwest China’s temperature over the past 250 years - Keyan Fang; Zhengtang Guo; Deliang Chen; Lei Wang; Zhipeng Dong; Feifei Zhou; Yan Zhao; Jinbao Li; Yingjun Li; Xinguang Cao (Climate Dynamics, 2019)

An interdecadal climate dipole between Northeast Asia and Antarctica over the past five centuries - Keyan Fang; Deliang Chen; Zhengtang Guo; Yan Zhao; David Frank; Maosheng He; Feifei Zhou; Feng Shi; Heikki Seppä; Peng Zhang; Raphael Neukom (Climate Dynamics, 2019)

Abrupt vegetation shifts caused by gradual climate changes in central Asia during the Holocene - Yan Zhao; YaoLiang Liu; ZhengTang Guo; KeYan Fang; Quan Li; XianYong Cao (Science China Earth Sciences, 2017)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)